2008
DOI: 10.1038/jp.2008.168
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions of birth weight in rural Uttar Pradesh, India: implications for care of low-birth-weight infants

Abstract: Effective implementation of interventions targeting low birth weight (LBW) and preterm infants, who contribute 60 to 80% of all neonatal deaths, requires an understanding of local people's perceptions of birth weight. This study was conducted to understand how birth weight is perceived in a lowresource setting, including the etiology, signs and care given to infants of various weights. In this qualitative research study, in-depth interviews and focus group discussions were conducted with recently delivered wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…This is in contrast to those who delivered in the facilities who were told by health workers that LBW babies are delicate and need special care. These results agree with findings in a rural Indian community which showed that birth weight per se was not considered a determinant of newborn health by the mothers, but mothers classified newborns basing on signs like level of feeding, vigour and alertness [15]. Therefore a baby who has a low birth weight but does not have any signs that cause concern to the mother is not likely to be taken to a health facility, which is a missed opportunity for the mother to receive health education on appropriate home care practices for LBW.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in contrast to those who delivered in the facilities who were told by health workers that LBW babies are delicate and need special care. These results agree with findings in a rural Indian community which showed that birth weight per se was not considered a determinant of newborn health by the mothers, but mothers classified newborns basing on signs like level of feeding, vigour and alertness [15]. Therefore a baby who has a low birth weight but does not have any signs that cause concern to the mother is not likely to be taken to a health facility, which is a missed opportunity for the mother to receive health education on appropriate home care practices for LBW.…”
Section: Discussionsupporting
confidence: 90%
“…It is also not known if mothers perceive LBW as a danger sign that requires taking the baby to a health facility or whether they know how to care for them at home. Although there is a considerable amount of research carried out on care of neonates in general [15], there are still few studies focusing on the perceptions about low birth weight and on how mothers care for these high risk babies especially in resource limited settings where much of the care is given at home. This study explored mothers’ knowledge and beliefs in recognizing LBW as well as their home care practices for LBW babies.…”
Section: Introductionmentioning
confidence: 99%
“…48,73 Additionally, in these settings, birth weight is not perceived to be an important determinant of newborn health, therefore LBW babies may not receive appropriate care, thus aggravating the risk. 74 …”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 99%
“…The focus in this paper is not to describe these gaps nor is it a detailed description of the types of constraints that interventions need to address and, where they exist, facilitators to closing these gaps; these are covered in the accompanying papers. [7][8][9]13,14 Also included in this volume are two papers detailing how specific formative research findings were used to make decisions about the content and delivery of the intervention. These papers cover the two main community-based approaches to reducing neonatal mortality, namely women's groups 11 and home visits by community-based volunteers.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…In settings where a substantial proportion of births take place at home, interventions promoting special care for LBW babies have three choices: (i) to include weighing babies, for example by giving community health workers (CHWs) scales and training them to weigh babies in their homes, preferably within 24 h of birth, to identify LBW babies; (ii) to use a proxy for LBW babies, such as babies perceived by the community to be 'at risk' (in the case of Uttar Pradesh and Ghana, this is likely to include premature babies and twins), although currently evidence is lacking as to the sensitivity and specificity of the possible proxies; or (iii) to promote the behavior for all babies. The latter is the approach being adopted in Uttar Pradesh, 9 with skin-to-skin contact being promoted for all babies.…”
Section: Lessons Learnedmentioning
confidence: 99%